Crystal structure of (4-methoxyphenyl)[(4-methoxyphenyl)phosphonato]dioxidophosphate(1−) 2-amino-6-benzyl-3-ethoxycarbonyl-4,5,6,7-tetrahydrothieno[2,3-c]pyridin-6-ium - Joel T. Mague; Shaaban K. Mohamed; Mehmet Akkurt; Sabry H. H. Younes; Essam K. Ahmed; Mustafa R. Albayati (Acta Crystallographica Section E: Crystallographic Communications, 2015)
The asymmetric unit of the title molecular salt, C17H21N2O2S+·C14H15O7P2−, comprises two cations and two anions. Each cation features an intramolecular N—H...O hydrogen bond, which closes an S(6) ring; in each case the hydropyridine ring adopts a half-chair conformation. In the anions, the dihedral angles between the aromatic rings are 64.1 (2) and 54.9 (2)°. In each case, the diphosphate groups are close to eclipsed [C—P...P—C pseudo-torsion angles = 11.6 (2) and −19.3 (2)°]. One of the methoxy groups in each anion is disordered over two orientations in a 0.539 (18):0.461 (18) ratio in one anion and 0.82 (2):0.18 (2) in the other. In the crystal, O—H...O and N—H...O hydrogen bonds link the components into [100] chains. Numerous C—H...O interactions cross-link the chains into a three-dimensional network.